Positive Fixed Point of Strict Set Contraction Operators on Ordered Banach Spaces and Applications - Meiqiang Feng; Xuemei Zhang; Weigao Ge (Abstract and Applied Analysis, 2010)
The fixed point theorem of cone expansion and compression of norm type for a strict set contraction operator is generalized by replacing the norms with a convex functional satisfying certain conditions. We then show how to apply our theorem to prove the existence of a positive solution to a second-order differential equation with integral boundary conditions in an ordered Banach space. An example is worked out to demonstrate the main results.